Time-course of coiling activity in zebrafish (Danio rerio) embryos exposed to ethanol as an endpoint for developmental neurotoxicity (DNT) - Hidden potential and underestimated challenges - Zindler, Florian; Beedgen, Franziska; Braunbeck, Thomas (Chemosphere, 2019)
Detection of developmental neurotoxicity (DNT) has been recognized as a major challenge by regulatory bodies and science. In search of sensitive and specific test methods, spontaneous tail coiling of embryonic zebrafish has been recommended as a promising tool for identification of DNT-inducing chemicals. The present study was designed to develop a protocol for a prolonged test to study neurotoxicity during the entire development of coiling movement in zebrafish embryos. Ambient illumination was found to modulate coiling activity from the very onset of tail movements representing the earliest behavioral response to light possible in zebrafish. In the dark, embryos displayed increased coiling activity in a way known from photokinesis, a stereotypical element of the visual motor response. Elevated coiling activity during dark phases allows for the development of test strategies that integrate later coiling movements under the control of a further developed nervous system. Furthermore, zebrafish embryos were exposed to ethanol, and coiling activity was analyzed according to the new test protocol. Exposure of embryos to non-teratogenic concentrations of ethanol (0.4-1%) resulted in a delay of the onset of coiling activity and heartbeat. Moreover, ethanol produced a dose-dependent increase in coiling frequency at 26h post-fertilization, indicating the involvement of neurotoxic mechanisms. Analysis of coiling activity during prolonged exposure allowed for (1) attributing effects on coiling activity to different mechanisms and (2) preventing false interpretation of results. Further research is needed to verify the potential of this test protocol to distinguish between different mechanisms of neurotoxicity.
Gesehen am 18.10.2019